Characteristics of atmospheric polychlorinated naphthalenes (PCNs) collected at different sites in northern Taiwan. (June 2018) - Dat, Nguyen-Duy; Chang, Kai-Siang; Chang, Moo-Been
Abstract: Ambient air samples were collected simultaneously at three sites in northern Taiwan using high-volume samplers during winter and summer to evaluate the atmospheric PCN characteristics including concentration, distribution, potential sources and gas/particle partitioning. The average concentration (Σ73 PCNs from di-to octa-CN) observed at industrial site is the highest (172 ± 111 pg m −3 ), while PCN levels measured at urban and rural sites are comparable (45.2 ± 8.20 and 45.9 ± 24.4 pg m −3, respectively). The PCN concentrations are higher in summer compared with those measured in winter for all three sampling sites. Gas-phase PCNs predominate in ambient air, accounting for 94 ± 6.0% of total concentration. Homologue distributions of PCNs measured at industrial site are different from two other sites for both gas and particulate phases, suggesting that different sources contribute to PCNs collected at industrial site. Based on the ratios of characteristic PCN congeners and fraction of Σcombustion-related PCNs/ΣPCNs, thermal processes are identified as major sources of PCNs at industrial site. PCNs collected at urban and rural sites are mixed sources of thermal emissions and evaporation, however, more influence of thermal sources in winter and more impact of evaporation sources in summer are observed. Results of the logKp -logPL relationship indicate that both adsorption and absorption govern gas/particle partitioning of atmospheric PCNs in northern Taiwan. Furthermore, the relationship between logKp and logKOA reveals that absorption is more important in governing gas/particle partitioning of PCNs in winter compared to summer. Graphical abstract: Image 1 Highlights: PCNs concentrations in summer are higher than that in winter at all three sites. Industrial site is of the highest PCNs concentration in both winter and summer. Thermal processes are major sources of PCNs collected. Both adsorption and absorption are important in governing gas/particle partitioning. Abstract : Higher levels of PCNs are found at industrial site compared with other two sites, which is mainly caused by thermal sources.